BETWEEN DREAMS AND REALITY: Migration of Brazilian women to Switzerland - Schuler, Flávia de Maria Gomes; Dias, Cristina Maria de Souza Brito (Revista da Escola de Enfermagem da USP, 2014)
The general objective of this article was to study the process of illegal migration of Brazilian women to Switzerland and, more specifically, to analyze the motivations for migration, the difficulties found upon arrival, the circumstances that led them to get married and lastly an evaluation of the whole experience. The methodology was based in a qualitative approach. The participants were eight Brazilian women that illegally migrated to Switzerland but now are married with Swiss or European men. They responded to an interview focused in the objectives of the study. The appreciation of the data was realized with Minayo´s Content Analysis. The motivations were related to a bettering of the financial situation. In the difficulties encountered, we can bring out illegality, language and prejudice. Regarding marriage, they married to stay legally in the country. Finally, the evaluation of the experience was negative for most participants.